Third-country effects of U.S. immigration policy - Agostina Brinatti; Xing Guo (Bank of Canada, 2023)
We study how the effects of U.S. restrictions on skilled immigration affect the Canadian economy and American workers' welfare. In 2017, the United States implemented a policy that tightened the eligibility criteria for U.S. visas. This was followed immediately by a trend break in the number of skilled immigrant admissions to Canada. We use quasi-experimental variation introduced by this policy over time and across immigrant groups, along with U.S. and Canadian visa applications data, to show that in 2018 visa applications for moving to Canada increased by 30% relative to the period before the restrictions were imposed. We then study how the restrictions affected Canadian firms. We use comprehensive Canadian administrative databases containing the universe of employer-employee linked records, immigration records, and international trade data. We find that Canadian firms that were relatively more exposed to the inflow of immigrants increased production, exports, and employment of Canadian workers. Finally, we study the policy's impact on American workers by incorporating immigration policy into a multi-sector international trade model. With international trade, the increase in immigration to other countries due to the restrictions affects American wages through U.S. exports and consumption prices. We calibrate the model using our novel data and reduced-form estimates. We find that the welfare gains for American workers targeted for protection by the 2017 policy are up to 25% larger in a closed economy than they are in an open economy with the observed trade levels.
Keywords: F16; F22; J61; 330; International topics; Labour markets; Recent economic and financial developments; Trade integration